The Perceptions of Students from Arabic Education Programs About Arabic Teaching Materials Containing Islam and Science in Madrasah - Mohammad Zaelani Musonif (Proceeding International Conference on Religion, Science and Education, 2023)
Islam and Science are often understood to be two different things, even though both have a firm relationship. Islam itself has a fairly intense relationship with Arabic. Therefore, it is important for learning Arabic to try to display Islamic values associated with science. This research aims to determine the perceptions of Arabic language education students about the urgency of Arabic teaching materials containing Islam and Science in Madrasas. The research used a qualitative method with the type of qualitative descriptive research. The data collection technique use questionnaire and literature study. The analysis of data was carried out by collecting, reducing, synthesizing, or interpreting data, and drawing conclusions. The research results: the content of Islam and Science is very important to be added to Arabic teaching materials in Madrasas. There were 37.5% of students who were respondents in this study totally agreed with adding Islam and science in Arabic teaching materials, 56.3% of students agreed, and there were only 6.3% of student respondents who disagreed with this. This is based on the content of Islam and Science which can increase the knowledge of students; embed students’ enthusiasm and motivation in learning Arabic, and become an Arabic learning contribution integrating the two things in an effort to counter the dichotomy of knowledge. Arabic teaching materials containing Islam and science are important and deserve to be developed in certain areas, such as vocabulary and texts, both at the both in Islamic elementary schools (MI), Islamic junior high schools (MTs), and Islamic senior high schools (MA) levels.